Assessing the Use of Water Hyacinth Ash to Harness Properties of Mortar for Use in Dampness-Prone Areas - Christopher Kalule Wosuula (Uganda Christian University, 2025)
This study investigates the potential of incorporating water hyacinth ash into mortar to improve its durability and resistance to dampness in Ugandan construction. Water hyacinth ash's unique properties, were leveraged to enhance mortar's performance (Tombado, 2023). We will perform scaled and staged laboratory tests to evaluate the physical and mechanical properties of mortar amended with WHA, including measures of compressive strength, water absorption, porosity, and efflorescence (the efflorescence often encountered in water damaged structures. (Antonio, n.d.).In addition, this study will investigate the micro-structural transformation brought by including WHA in the mortar matrix. We will observe the pozzolanic reaction between the WHA and calcium hydroxide wrote during cement hydration by employing techniques such as scanning electron microscopy and X-ray diffraction (Kibwami, 2016).Alongside the technical assessment, the study will also evaluate the environmental and economic impact from the utilization of WHA in construction. A preliminary life cycle assessment will be completed to compare the energy consumption and carbon footprints of WHA to traditional cement in their respective production and realization. Lastly, a cost-benefit analysis will assess if WHA represents a cheaper solution for making mortar in areas with an abundance of water hyacinth and where a focussed waste-removal effort would be appreciated. (Barbhuiya, 2023) (Vedartham, 2023).In conclusion, this extended research seeks to provide a firm scientific foundation for the use of water hyacinth ash as a sustainable and natural supplement to improve the performance of mortar in Uganda in areas prevalent with dampness.
Undergraduate